Investigating the Effects of Solution Treatment Parameters and Artificial Aging on Hardness Improvement of Precipitation-Hardened 6061 Aluminum Alloy - Yunus, Azwar; Akhyar, Akhyar; Hasanuddin, Iskandar; Sasmito, Agus (Politeknik Negeri Lhokseumawe, 2025)
This study investigates the impact of solution treatment parameters such as temperature, holding time, and quenching media on the hardness enhancement of wrought aluminum alloy 6061-T6 through precipitation hardening. The objectives of this research are to analyze the influence of solution treatment parameters on hardness enhancement, explore the correlation between the solutioning step and the artificial aging process, and optimize the heat treatment process for improved hardness values. Specimens of 6061-T6 aluminum alloy initially exhibited a hardness of 102 HV. After heating to 500°C with holding times of 45, 60, and 75 minutes, followed by quenching in water and SAE 40 oil, Vickers hardness testing revealed significant changes: hardness dropped to 52 HV after solution treatment, then increased to 63 HV (21.15% increase) for 60 minutes and 64 HV (23.08% increase) for 75 minutes. After artificial aging at 210°C for 120, 180, and 240 minutes, the maximum hardness recorded was 113 HV, marking a 10.78% increase from the initial hardness. The quenching medium also influenced hardness; specimens quenched in SAE 40 oil showed improved hardness compared to those quenched in water, likely due to slower cooling rates that allow for better precipitate formation. The increase in hardness is closely linked to microstructural changes during heat treatment. Solution treatment promotes the dissolution of alloying elements, leading to the formation of fine precipitates during aging. These precipitates impede dislocation movement, enhancing the alloy's strength through precipitation hardening. Thus, the density and distribution of these precipitates significantly contribute to the overall hardness enhancement observed in the 6061-T6 aluminum alloy